2009
DOI: 10.2169/internalmedicine.48.1540
|View full text |Cite
|
Sign up to set email alerts
|

Pure Dysarthria Resulting from a Small Cortical Infarction Located at the Left Middle Frontal Gyrus

Abstract: Pure dysarthria caused by a small cortical infarction is rare. Recent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Pure dysarthria as a result of an isolated stroke to the middle frontal gyrus has been reported. 43 A recent surgical study showed that of 151 patients who had electrocortical stimulation testing in the portion of the DLFPC just superior to Broca area showed anomia in anywhere between 3.6% and 10.8% of patients stimulated depending on the location within the middle frontal gyrus and region of the inferior frontal sulcus. 44 However, the same study also shows 10 regions within the middle frontal gyrus where 100% of patients stimulated did not show interruptions of speech.…”
Section: Frontal Language Mappingmentioning
confidence: 99%
“…Pure dysarthria as a result of an isolated stroke to the middle frontal gyrus has been reported. 43 A recent surgical study showed that of 151 patients who had electrocortical stimulation testing in the portion of the DLFPC just superior to Broca area showed anomia in anywhere between 3.6% and 10.8% of patients stimulated depending on the location within the middle frontal gyrus and region of the inferior frontal sulcus. 44 However, the same study also shows 10 regions within the middle frontal gyrus where 100% of patients stimulated did not show interruptions of speech.…”
Section: Frontal Language Mappingmentioning
confidence: 99%
“…The left middle frontal gyrus region (BA 6) of the brain has traditionally been associated with roles in planning and coordination of motor movements, but recent studies have also shown that its dysfunction can result in dysarthria or dysgraphia. [39][40][41] Disconnection between the left middle frontal gyrus visual processing centers such as the lingual gyrus and cuneus can presumably result in difficulties with processing or production of written language. Indeed, in a study comparing neurocognitive function between right and left sided UCS patients, left sided patients performed significantly worse in spelling.…”
Section: Discussionmentioning
confidence: 99%
“…The right primary visual cortex exhibited decreased connectivity to the bilateral superior parietal lobules and adjacent posterior brain structures as well. The left middle frontal gyrus region (BA 6) of the brain has traditionally been associated with roles in planning and coordination of motor movements, but recent studies have also shown that its dysfunction can result in dysarthria or dysgraphia 39–41 . Disconnection between the left middle frontal gyrus visual processing centers such as the lingual gyrus and cuneus can presumably result in difficulties with processing or production of written language.…”
Section: Discussionmentioning
confidence: 99%